If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + 5 = 2p + 15 Reorder the terms: 5 + 3p = 2p + 15 Reorder the terms: 5 + 3p = 15 + 2p Solving 5 + 3p = 15 + 2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2p' to each side of the equation. 5 + 3p + -2p = 15 + 2p + -2p Combine like terms: 3p + -2p = 1p 5 + 1p = 15 + 2p + -2p Combine like terms: 2p + -2p = 0 5 + 1p = 15 + 0 5 + 1p = 15 Add '-5' to each side of the equation. 5 + -5 + 1p = 15 + -5 Combine like terms: 5 + -5 = 0 0 + 1p = 15 + -5 1p = 15 + -5 Combine like terms: 15 + -5 = 10 1p = 10 Divide each side by '1'. p = 10 Simplifying p = 10
| 8*x=72 | | -7(f+1)-6=-41f+55 | | x(x-3)(x+3)=0 | | .4y=9 | | 2z+3(x-5)=130 | | 8y-4=36 | | 2x^3-2x^2+6x-6=0 | | 7x-2=-21 | | c(N)=25+0.15 | | 5x^2-40+20=0 | | 9=2+6.7+.6Y | | 8timesx=72 | | 25+3h=49 | | 2,4(x-0,1)-0,26=2,4x-0,4 | | q(3q+4)=4 | | 15y+8=14 | | 6(3+x)=8(x-20) | | 1.6+.6Y+2=.9 | | 18A=4A+98 | | 5x+2(4-3x)=-7 | | 7(-5)+2(8)=-19 | | 1.6+.6Y+2=.6Y | | 3l+5=4l+2.5 | | (3w+2)*(3w-2)= | | (1+x)+x=1.1 | | 9T+12T=105 | | [y-4]=6 | | x^2+26x-60= | | (3w+2)(3w-2)= | | x+x+x-6=48 | | (4x-3y)(2x+y)= | | .7x+1.5=3.88 |